Analysis and experiment on cutting performances of high-stubble maize stalks - Jiale, Zhao; Dongyan, Huang; Honglei, Jia; Jian, Zhuang; Mingzhuo, Guo (International Journal of Agricultural and Biological Engineering, 2017)
In the cold areas of Northeast China, maize high-stubble cutting is a novel stalk conservation tillage method, in which the maize stalks are under a unilaterally-fixed no-support cutting status. Thus, reducing the cutting resistance and power consumption of maize stalks under this status is very significant for development of high-efficiency high-stubble cutting devices. Based on a self-designed testing system that highly restored the maize high-stubble cutting conditions and by means of experimental design and mathematic statistics, the effects of working parameters (blade angle, blade shape, cutting speed and cutting angle) on the maximum cutting resistance and power consumption were studied. By analyzing stress conditions during the stalk cutting process, six mathematic models were built to express the relationships between individual factors and the maximum cutting resistance or cutting power consumption. Through model optimization, the parameter combination for optimal cutting performance of maize stalks under unilaterally-fixed no-support cutting status was obtained: blade angle is 18°, blade shape is isosceles triangle, cutting speed is 9.5 m/s, and cutting angle is 75°. Field validation experiments under this parameter combination showed that the maximum cutting resistance was (55.23±3.50) N (declined by 11.04%), and power consumption was (11.41±1.04) J (declined by 16.65%). The research findings can be a reference for the design and development of maize high-stubble cutting devices.Keywords: cutting performances, blade angle, working parameters, high-stubble, conservation tillage, mechanism analysis, cornDOI: 10.3965/j.ijabe.20171001.2589Citation: Zhao J L, Huang D Y, Jia H L, Zhuang J, Guo M Z. Analysis and experiment on cutting performances of high-stubble maize stalks. Int J Agric & Biol Eng, 2017; 10(1): 40－52.